The Myths of Babad Banyumas in The View of Health, Social and Ecological Wisdom - Darmawan Edi Winoto (JSSH (Jurnal Sains Sosial dan Humaniora), 2018)
Babad Banyumas (BU) contains the facts and  myths of an event that occurred in the past. BU contains facts about the establishment of the Banyumas region in Central Java and the myths surrounding the stories in it. The facts and interpretations in the BU have been widely studied by academics. On the other hand, the myths in the BU are not studied by academics yet. The myth loses its meaning when faced in this modern era. This study aims to explore the myths in Babad Banyumas. The myth is further interpreted in relation to the field of health, social and ecological wisdom in the current context. Deconstruction and qualitative method with BU text content analysis were used in this research. Data collection was done through observation and interview of some experts. Qualitative data analysis using display data, data reduction and data verification to find common themes were also used as data analysis in this research. The results of the study found that there were four myths in Babad Banyumas, namely cucumber myths, jungle fowl, pendhapa displacement, and  myth of having marriage relationship with Dipayuda III. These myths include health, social and ecological wisdom messages.